INFECTION PREVENTION AND CONTROL TRAINING AMONG HEALTHCARE WORKERS: A SURVEY OF GAPS AND IMPLICATIONS FOR PRACTICE AT A NAMIBIAN HOSPITAL (Proceedings of the International Conference on Public Health, 2025)
Infection prevention and control is crucial in preventing the spread of infections in hospital settings and healthcare workers play a vital role in preventing such healthcare associated infections. However, globally, hospitals in low- and middle-income countries experience challenges in infection prevention and control. Such challenges shown in private hospitals to be attributed to a “lack of trained staff”, and insufficient information and technology support, which therefor necessitate research in public settings. A quantitative cross-sectional study was conducted at a hospital in Namibia using non-probability convenience sampling to recruit 118 healthcare workers as participants. The study looked to identify gaps in the training of healthcare workers in infection prevention and control at the hospital. A self-administered pre coded questionnaire with was used as the research instrument to collect data. Data collected was entered on a customised Microsoft excel spreadsheet before being exported to Statistical Package for Social Science version 28 for analysis. Notably, 23% of participants felt that they had not received enough training in infection prevention and control practices during their training as health professionals. A considerable 55.9% of participants did not receive training in infection prevention and control when they started working at the hospital. In addition, 53.4% of participants did not receive any training on proper selection and use of personal protective equipment. Significantly, 71.2% of participants did not receive any follow-up training in infection prevention and control at the hospital. The study findings highlight the need for improvement in programmes targeted at training of healthcare workers on infection prevention and control in hospitals. Such training remains critical during clinical practice whilst training to be healthcare professionals, at entry into healthcare service and continuously along the provision of healthcare service to curb and prevent the spread of infections amongst patients, healthcare workers themselves and visitors to the hospitals.
Keywords: infection control; healthcare workers; hospitals; infection prevention and control; hospital training; hospital infection control